Spatial analysis of ice phenology trends across the Laurentian Great Lakes region during a recent warming period - Olaf P. Jensen; Barbara J. Benson; John J. Magnuson; Virginia M. Card; Martyn N. Futter; Patricia A. Soranno; Kenton M. Stewart (Limnology and Oceanography, 2007)
We examined spatial patterns of trends in ice phenology and duration for 65 waterbodies across the Great Lakes region (Minnesota, Wisconsin, Michigan, Ontario, and New York) during a recent period of rapid climate warming (1975‐2004). Average rates of change in freeze (3.3 d decade −1 ) and breakup (22.1 d decade −1 ) dates were 5.8 and 3.3 times more rapid, respectively, than historical rates (1846‐1995) for Northern Hemisphere waterbodies. Average ice duration decreased by 5.3 d decade −1 . Over the same time period, average fall through spring temperatures in this region increased by 0.7°C decade −1 , while the average number of days with snow decreased by 5.0 d decade21, and the average snow depth on those days decreased by 1.7 cm decade −1 . Breakup date and ice duration trends varied over the study area, with faster changes occurring in the southwest. Trends for each site were compared to static waterbody characteristics and meteorological variables and their trends. The trend toward later freeze date was stronger in large, low‐elevation waterbodies; however, freeze date trends had no geographic patterns or relationships to meteorological variables. Variability in the strength of trends toward earlier breakup was partially explained by spatial differences in the rate of change in the number of days with snow cover, mean snow depth, air temperature (warmer locations showed stronger trends), and rate of change in air temperature. Differences in ice duration trends were explained best by a combination of elevation and the local rate of change in either temperature or the number of days with snow cover.